2010
DOI: 10.1093/jjco/hyq075
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Trends and Incidence and Mortality Patterns in Turkey

Abstract: Cancer incidence and mortality rates have been increasing in Turkey as most of the developing countries. Besides socioeconomic factors, one of the most prominent attributes of developing countries is the dissimilarity of their age-dependent demographic structure. In Turkey, cancer incidence rates rise due to individual and environmental risk factors as well as due to the improvement in the registry system and to increase in access to health services. According to the data retrieved from the Ministry of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 7 publications
3
36
0
4
Order By: Relevance
“…In our country, cancer has the highest mortality rate after cardiovascular diseases (Yilmaz et al, 2011). The reasons for high cancer mortality include insufficient and/or incorrect information about cancer formation, diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our country, cancer has the highest mortality rate after cardiovascular diseases (Yilmaz et al, 2011). The reasons for high cancer mortality include insufficient and/or incorrect information about cancer formation, diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality rates of the cancer types seen in our country vary according to age and gender (Yilmaz et al, 2011). According to the Turkey Almanac of Statistics 2012 Report, the incidence of cancer in our country was 280.5 in a hundred thousand in men and 172.0 in a hundred thousand in women in 2008.…”
Section: Introductionmentioning
confidence: 86%
“…18,19 In our re gi on, gas tric can cer is the 6 th most com mon can cer in both se xes. 20 The ma jo rity of gas tric can cer ca ses are aged bet we en 50 and 70 years. Ma les de ve lop gas tric can cer ap pro xi ma tely twi ce mo re fre qu ently com pa red to fe ma les.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence was decreased from 32/100 000 in 1940's to 8.3/100 000 in 1980. The Pap smear test is a simple, non-invasive, and a cost-effective method for the diagnosis of cervical and vaginal precancerous, cancerous lesions [3]. According to a study made by the International Agency for Research on Cancer in 2002, the cervical cancer incidence rate in Turkey was 4.5/100 000, it was estimated to encounter 1364 new cervical cancer cases and 726 of the reported deaths were associated with cervical cancer in the same year [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study made by the International Agency for Research on Cancer in 2002, the cervical cancer incidence rate in Turkey was 4.5/100 000, it was estimated to encounter 1364 new cervical cancer cases and 726 of the reported deaths were associated with cervical cancer in the same year [2]. In 2003, the results of studies performed by the Turkish Ministry of Health, department of cancer control in eight cities were published [3]. This study showed that cervical cancer ranks the 10 th among all women's cancers and its incidence rate is 4.76/100 000 [3].…”
Section: Introductionmentioning
confidence: 99%